Caveolae disassemble upon membrane lesioning and foster cell survival - Štefl, Martin; Takamiya, Masanari; Middel, Volker; Tekpınar, Miyase; Nienhaus, Karin; Beil, Tanja; Rastegar, Sepand; Strähle, Uwe; Nienhaus, Gerd Ulrich (iScience, 2024)
Repair of lesions in the plasma membrane is key to sustaining cellular homeostasis. Cells maintain cytoplasmic as well as membrane-bound stores of repair proteins that can rapidly precipitate at the site of membrane lesions. However, little is known about the origins of lipids and proteins for resealing and repair of the plasma membrane. Here we study the dynamics of caveolar proteins after laser-induced lesioning of plasma membranes of mammalian C2C12 tissue culture cells and muscle cells of intact zebrafish embryos. Single-molecule diffusivity measurements indicate that caveolar clusters break up into smaller entities after wounding. Unlike Annexins and Dysferlin, caveolar proteins do not accumulate at the lesion patch. In caveolae-depleted cavin1a knockout zebrafish embryos, lesion patch formation is impaired, and injured cells show reduced survival. Our data suggest that caveolae disassembly releases surplus plasma membrane near the lesion to facilitate membrane repair after initial patch formation for emergency sealing.
Gesehen am 26.07.2024